Pengaruh Corporate Social Responsibility Disclosure, Diversifikasi Perusahaan, Kompensasi Bonus, dan Kualitas Audit Terhadap Earnings Management - Nolita Yeni Siregar; Yulis Veronika (Jurnal Akuntansi dan Keuangan, 2017)
This study was aimed at examining the influence of corporate social responsibility disclosure, corporate diversification, bonus compensation and quality audit as independent variables on earnings management as the dependent variable. Earnings management was measured using the discretionary accrual. The population in this study was all manufacturing companies listed in the Indonesia Stock Exchange in the period of 2013-2015. The sampling technique in this study used purposive sampling, in order to obtain a sample of 64 companies. The analytical method used was multiple linear regression with SPSS version instrument 20. The study results and discussion proved that corporate social responsibility disclosure and bonus compensation had an effect on the earnings management. Meanwhile, corporate diversification and quality audit had no effect on the earnings management.